2020
DOI: 10.1177/0954406220976704
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of heat and mass transfer in a Maxwell fluid

Abstract: The objective of current research is to analyze the MHD flow of a Maxwell fluid towards a stretching sheet with thermophoretic and stratification effects. The analysis of heat and mass transfer is presented in the presence of variable thermal conductivity and the Cattaneo-Christov theory. The Cattaneo-Christov theory is used instead of Fourier and Fick laws because Fourier and Fick's laws give parabolic equations, which propagate in the space with infinite speed. The under-consideration flow model is converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Hayat et al 32 observed Maxwell Fluid steady flow with convective boundary conditions. Khan et al 33 explored the mathematical study of double-diffusive in a Maxwell fluid. Muhammad et al 34 explored the combined impacts of heat and mass transfer on Maxwell fluid MHD free convection flow with variable temperature and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al 32 observed Maxwell Fluid steady flow with convective boundary conditions. Khan et al 33 explored the mathematical study of double-diffusive in a Maxwell fluid. Muhammad et al 34 explored the combined impacts of heat and mass transfer on Maxwell fluid MHD free convection flow with variable temperature and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they explained the behavior of thermophoretic diffusive deposition velocity over diverse pertinent parameters. Khan et al 12 numerically analysed the thermophoretic and stratification effects on stream of a Maxwell liquid towards an extending sheet. Here, they explored the consequence of thermophoretic effect on fluid velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the analysis of Williamson nanofluid flow over stretching sheet was studied by Nadeem and Hussain (2014). Several researchers, Khan et al (2020b), Khana et al (2020), Kh et al (2018c), Ahmad et al (2020) and Nadeem et al (2020), Nadeem et al (2014), investigated the flow of non-Newtonian fluids in different situations.…”
Section: Introductionmentioning
confidence: 99%